El Pobre Llàtzer i el si d'Abraham en l'art monumental de la Catalunya romànica - Pagès i Paretas, Montserrat (Miscel·lània litúrgica catalana, 2007)
This paper deals with the several extant versions of the parable of Lazarus and Dives in the Romanesque art of Catalonia, in mural painting and in stone sculpture, either complete or almost (as in the Ripoll portal and the cloisters of Sant Cugat del Vallès and of the cathedral of Girona) or with a single image. The bosom of Abraham, as a figure of Paradise, appears in Sant Joan de Boí and in Sant Romà d?Aineto. The feast of the rich man of Sant Pere de Sorpe was part of a more enlarged cycle, and in Sant Climent de Taüll the dives?s table (in situ) was placed in front of the poor Lazarus (MNAC), in a very interesting and original program.